Penggunaan Instrumen Penilaian Psikomotor Siswa Pada Praktikum Kimia Berbasis Kurikulum 2013 - Yunita, Luki; Irwandi, Dedi; Pertiwi, Diah Ayu (Jurnal Riset Pendidikan Kimia (JRPK), 2017)
This study attempts to develop research instruments the psychomotor lab work chemical the electrolyte solution and nonelectrolyte. On the feasibility and knows, the assessed by an observer. Model 4D stage used to define, design, development, and disseminate. This research is bounded reached the stage of development. Feasibility an instrument used in research of chief consisting of seven aspects with the each every aspect which is language 89,14 %, construction 89,71 %, 86,43 % matter, objectifies 86,67 %, systematic 84,29 %, practical 92,17 %, and funding of the 85,71 %. The technique of data analysis includes data processing and instrument reliability assessment by the observer. The results of this research and development show that assessment instrument was developed to have a reliability of 0.89 and meet excellent quality based on an assessment of observer with the percentage of 87.73%. Thus, psychomotor aspects of assessment instruments are viable and can be used as one of the assessment tools in chemical teaching material on activities of the electrolyte solution and nonelectrolyte. Keywords: Assessment instrument, Psychomotor, lab work chemical